2015
DOI: 10.1080/19942060.2015.1004819
|View full text |Cite
|
Sign up to set email alerts
|

A three dimensional inSILICOmodel for the simulation of inspiratory and expiratory airflow in humans

Abstract: A three-dimensional, computational fluid dynamics model of the human respiratory system is put forward for consideration. This in silico model is based on existing state-of-the-art geometric approximations. As a complete simulation of the geometry would have unaffordable high computational costs, the model is composed of a single path of air from the mouth to the 16th bronchial generation, truncating the symmetrical branches that were not included. The innovation housed in this model is the development of a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
11
0
6
Order By: Relevance
“…After truncation, appropriate boundary conditions are imposed on the truncated sections by applying prior pressure conditions or stochastically coupled boundary conditions. A truncated model was used by Tena et al (2015) whereby the same velocity vector fields were imposed on the truncated sections as the corresponding sections of the developed branches of the airway. In another study by Walters and Luke (2010), where 50% of the airway paths were truncated, static pressure values at corresponding sections of the remaining bifurcations were used as the boundary conditions at the truncated sites.…”
Section: Whole Lung Airway Model Vs Localized Simulationsmentioning
confidence: 99%
“…After truncation, appropriate boundary conditions are imposed on the truncated sections by applying prior pressure conditions or stochastically coupled boundary conditions. A truncated model was used by Tena et al (2015) whereby the same velocity vector fields were imposed on the truncated sections as the corresponding sections of the developed branches of the airway. In another study by Walters and Luke (2010), where 50% of the airway paths were truncated, static pressure values at corresponding sections of the remaining bifurcations were used as the boundary conditions at the truncated sites.…”
Section: Whole Lung Airway Model Vs Localized Simulationsmentioning
confidence: 99%
“…The upper part of the bronchial tree with well-described morphometric data is reviewed in several papers [3][4][5][6][7][8][9][10][11][12][13][14][15]. An advanced review of these investigations can be found in [2].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant graph of the bronchial tree contains up to seven generations. Two torus configurations were used to design an individual bifurcation in [7][8][9] (Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
“…V. 14. № 2. doi: 10.17537/2019.14.635of symmetric dichotomy (symmetric bronchial tree model[1]) are defined by the following formulas[9]:• input bronchus radius (in mm)…”
mentioning
confidence: 99%